Pengaruh Cash Turnover, Receivable Turnover, dan Inventory Turnover Terhadap Return On Asset Perusahaan Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2013 – 2015 - Linda Vania Wijaya; Lauw Tjun Tjun (Jurnal Akuntansi, 2017)
Abstract Working capital is the sum of current assets owned by the company such as cash, marketable securities, accounts receivable, and inventory that is always spinning to get revenue. The purpose of this study was to examine and analyze (1) the effect of Cash Turnover, Receivable Turnover and Inventory Turnover on Return On Assets, (2) the effect of Cash Turnover on Return On Assets, (3) the effect of Receivable Turnover on Return On Assets, and (4) the effect of Inventory Turnover on Return on Asset on the food and beverage sector companies listed on Indonesia Stock Exchange in 2013-2015 period. Samples taken in this study using purposive sampling method. Data collected by recording the document, and then analyzed using multiple linear regression analysis,            F test, and t test. Results showed that simultaneous Cash Turnover, Receivable Turnover and Inventory Turnover affect the Return On Assets. While partially, it was found that only Cash Turnover and Inventory Turnover affecting the Return On Asset. Keywords:  Cash Turnover; Inventory Turnover; Receivable Turnover; Return  On Asset